Extraction, structural characterization, and antioxidant activity of polysaccharides derived from Arctium lappa L. - Gao, Dandan; Chen, Hong; Li, Haixing; Yang, Xuhua; Guo, Xingchen; Zhang, Yuxuan; Ma, Jinpu; Yang, Jutian; Ma, Shuwen (Frontiers in Nutrition, 2023)
Introduction Arctium lappa L. root has high nutritional and medicinal values and has been identified as a healthy food raw material by the Ministry of Health of the People's Republic of China. Methods In the present study, an aqueous two-phase system (ATPS) of polyethylene glycol (PEG)-(NH4)2SO4 was used to extract Arctium lappa L. polysaccharides (ALPs) from the Arctium lappa L. roots, the optimal extraction conditions of crude ALPs were optimized by using the single-factor experiment and response surface methodology. The structure and composition of ALPs were determined by fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and high-performance liquid chromatography (HPLC). At the same time, the antioxidant activity of ALPs was investigated by in vitro antioxidant experiment. Results The optimized extraction parameters for extraction ALPs were as follows: the PEG relative molecular weight of 6,000, a quality fraction of PEG 25%, a quality fraction of (NH4)2SO4 18%, and an extraction temperature of 80°C. Under these conditions, the extraction rate of ALPs could reach 28.83%. FTIR, SEM and HPLC results showed that ALPs were typical acidic heteropolysaccharides and had uneven particle size distribution, an irregular shape, and a rough surface. The ALPs were chiefly composed of glucose, rhamnose, arabinose, and galactose with a molar ratio of 70.19:10.95:11.16:6.90. In addition, the ALPs had intense antioxidant activity in vitro with IC50 values in the ·OH radical (1.732 mg/ml), DPPH radical (0.29 mg/ml), and superoxide anion (0.15 mg/ml) scavenging abilities. Discussion The results showed that ATPS was an efficient method to extract polysaccharides and could be used for the extraction of other polysaccharides. These results indicated that ALPs had great prospects as a functional food and could be exploited in multiple fields.